A method based on impedance spectroscopy for predicting the behavior of novel ionic liquid-polymer inclusion membranes in microbial fuel cells. (September 2015) - Salar-García, M.J.; Ortiz-Martínez, V.M.; de los Ríos, A.P.; Hernández-Fernández, F.J.
Abstract: MFCs (microbial fuel cells) are an emerging technology for simultaneous treatment of wastewater and energy recovery. These devices exploit microbial metabolism to generate electricity from organic matter. The separator is a critical factor in the design of MFCs as it plays a crucial role in the transport of protons from the anode to the cathode, affecting the performance of the cell. It is thus of interest to develop a method to predict the behavior of a separator before being used in MFCs. The present work proposes a new method based on spectroscopy to calculate the internal resistance of several PIMs (polymer inclusion membranes) based on ILs (ionic liquids) and predict their behavior as novel proton exchange membranes in MFCs. Four types of PIMs based on three different groups of ionic liquids were prepared and electrochemically characterized: Methyltrioctyl ammonium chloride, [MTOA + ][Cl − ], 1-methyl-3-octylimidazolium hexafluorophosphate, [OMIM + ][ PF 6 − ], Tri-butylmethylphosphonium methylsulphate, [ P 4, 4, 4, 1 + ][ MeSO 4 − ], and Triisobutyl-(methyl)-phosphonium tosylate, [ P I 4, I 4, I 4, 1 + ][TOS − ], some of which were patented by our research group to be used as separator in MFCs (P201330453). Finally, the PIMs were evaluated in MFCs for energy production and wastewater treatment and compared with Nafion ® 117. The results show that the [ P I 4, I 4, I 4, 1 + ][TOS − ]-based membrane outperformed the rest of separators in terms of power output. Highlights: Characterization of polymer inclusion membranes based on ILs (ionic liquids). EIS technique for predicting the behavior of novel IL-based separators in MFCs. Assessment of IL-based microbial fuel cells for wastewater treatment. Similar performance achieved by MFCs using [ P I 4, I 4, I 4, 1 + ][TOS − ] and Nafion ® 117.